Investigation of passive bearing for biomedical applications - Tham, Denise Wai Xi (2017)
The Muijderman Equation was the basis for geometry modifications in this project. This was aimed at achieving positive pressure generation between the rotating spiral groove bearing and the stationary housing for hydrodynamic lift with varying geometrical parameters when the axial clearance gap between the two is 0.2mm.